Effects of Dietary Supplementation of Garlic and Oregano Essential Oil on Biomarkers of Oxidative Status, Stress and Inflammation in Postweaning Piglets - Jorge Rivera-Gomis; Camila Peres Rubio; Cristina Martínez Conesa; Julio Otal Salaverri; José Joaquín Cerón; Damián Escribano Tortosa; María José Cubero Pablo (Animals, 2020)
The effects of two different concentrations of micro capsuled oregano essential oil (OEO) and purple garlic powder on biomarkers of oxidative status, stress, and inflammation, as well as on average daily gain (ADG) and feed conversion ratio (FCR), were evaluated in piglets during the postweaning period. The trial was carried out with 300 crossbred pigs of 21 days of age fed with different concentrations of OEO and purple garlic powder and ZnO. Saliva and serum samples were taken to evaluate a panel of biomarkers of oxidative status, stress, and inflammation. OEO and garlic powder at 0.4% did not produce significant changes in C-reactive protein (CRP) and cortisol and yielded higher levels of the antioxidant biomarker CUPRAC in serum than higher doses (p < 0.01); they yielded a better ADG than the control and ZnO diets. OEO and garlic powder at higher concentrations than 0.4% showed higher concentrations of CRP (p < 0.05). Overall, doses of OEO and garlic powder at 0.4% did not lead to inflammation, stress, or negative changes in oxidative biomarkers in piglets during the postweaning period and gave better productive performance than the control and ZnO diets. High doses of OEO and garlic powder were ineffective and could negatively affect the animals. Therefore, our results highlight the importance of the dose used when OEO or garlic are supplemented to piglets.